Editorial – Foreword to the 2025 Special Compilation on “Family Therapy and Family Studies in Supporting Mental Health" - Dávid, Beáta; Danis, Ildikó (European Journal of Mental Health, 2025)
Harmonious and resilient relationships within couples and families contribute to the wellbeing and life satisfaction of individuals as well as to the strength of societies. Conversely, chronic challenges and difficulties in close relationships and family functioning can make individuals and wider communities vul nerable (Li et al., 2025; Walsh, 2016). Systemic family therapy, combined with informal support from family members and their communities, can be an effective intervention in child and family protection (Hertlein, 2023). The Special Call titled “Family Therapy and Family Studies in Supporting Mental Health” was announced in 2024 following a significant period of population stress in recent years, during which family resilience and support were of paramount importance globally due to health crises, natural disasters, geopolitical conflicts, wars, and economic hardships. The peer reviewed and edited articles were published throughout the year, and we are now publishing the entire Special Compilation at the beginning of the academic year. In addition to other publications in our journal, this 2025 Special Compilation features five articles. In this short editorial foreword, we – a sociologist and a psychologist – aim to present some interdisciplinary thoughts on contemporary family life, family studies, and family interventions.